Adaptive mechanisms of development of integration processes in accounting (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The main purpose of the research study, the fact that management of financial activity is apparentreliability, simplicity and precision of the integration processes in the accounting system.In the article the new approach, which aims neoinstitutsional economy, evolutionary approach tothe financial information and information theory, so that we can learn about the center of the enterpriseinformation integration processes, which can give a good description of the development of new approaches,their features as an automated accounting system and the development of effective integrationinto the modern-looking forms of generalization and introduction of emission methods.The main feature of this study is to characterize new approaches to economic information and thetheory of evolution, which is an information and financial integration processes at the center of a campaignof corporate information.